The murky circumstances of consent in Canada: a commentary on R. v Kirkpatrick - Wright, JJ (Jessica); Zidenberg, Alexandra M.; Varsanyi, Stephanie; Macaulay, Kaelyn; Sanabria, Sara (My University, 2025)
The Supreme Court of Canada recently ruled on R. v Kirkpatrick, a case that raises many complex questions regarding consent and sexual violence in Canada. Despite the complainant stating that she would only have sexual intercourse with Ross Kirkpatrick with a condom, Kirkpatrick chose not to wear one, and he was charged with sexual assault. While at trial, it was found that the complainant consented to the sexual activity, and the BC Court of Appeal subsequently disagreed with that finding. Ultimately, the Supreme Court of Canada held that, when both parties agree to use a condom, the removal of the condom by one party is not consensual and constitutes sexual assault. In this commentary, we discuss how this case highlights the murky circumstances of consent in Canada, with particular attention to the growing phenomenon of “stealthing.” We lay out the key jurisprudence leading up to Kirkpatrick—namely, R. v Hutchinson and R. v Mabior. Then, we outline the state of the framework on consent in Canada, and we critique the legal tests for vitiating consent through fraud. We conclude that the definition of sexual activity to which an individual consents must consider essential conditions such as condom use.
Keywords: stealthing; Canada; sexual assault; consent; vitiating consent